Kesantunan Berbahasa Kisah Nabi Yusuf dalam Al-Qur’an: Pendekatan Brown dan Levinson - Ritonga, Ridwan; Munawaroh, Izati (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
This article examines the concept of language politeness in the story of the Prophet Yusuf in the Qur'an using the approach of politeness theory by Brown and Levinson. This study explores the character of the Prophet Yusuf and his interactions with various characters in the Qur'an, focusing on aspects of language politeness manifested in conversations and dialogues. The method of analysis used is discourse analysis, this article identifies the communicative strategies used by the Prophet Yusuf in various situations, as well as how the concept of politeness is reflected in his actions and speech. The findings of this study are expected to provide a deeper understanding of how politeness values are manifested in the Qur'an and their relevance in contemporary social and cultural contexts. As such, this article makes an important contribution to the understanding of the principles of communication upheld in Islamic teachings and their application in everyday life.